PERAN DRONE MILITER DALAM MENGUBAH STRATEGI PERANG MODERN: STUDI KASUS PERANG UKRAINA-RUSIA DAN PERANG ARMENIA-AZERBAIJAN - Rofii, Muhammad Syaroni (Universitas Jenderal Ahmad Yani, 2025)
Drones have transformed into a critical variable in modern warfare. As a weapon, drones possess the capability to support the success of military operations and even win wars, whether for offensive or defensive purposes. Using a qualitative research method, this study seeks to explain the role of drones in modern battlefields by examining the case studies of the Azerbaijan-Armenia War in 2020 and the Russia-Ukraine War from 2022 to 2024. These cases illustrate how drones have played a key role in reconnaissance and attacks. This study also concludes that amidst the ongoing military conflicts, drones have sparked debates among state leaders and experts regarding their excessive use, as drones are often misused, violating the concept of just war. Furthermore, the use of drones by various countries for both civilian and military purposes has prompted technology manufacturers to offer new products that are believed to provide solutions for military operations as well as civilian needs.